2022
DOI: 10.2147/ijgm.s350474
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Triglyceride Glucose Index and the Risk of First Stroke in Elderly Hypertensive Patients

Abstract: Background: Several recent studies have shown the relationship between the triglyceride glucose (TyG) index and the risk of stroke in the general population and in a few patient cohorts; however, the role of the TyG index on stroke risk in elderly hypertensive patients has not been determined. Thus, we aimed to investigate the association of the TyG index with first stroke and first ischemic stroke in elderly individuals with hypertension. Methods: We included 8487 elderly subjects with hypertension from the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…In this study, trajectories were used to present the TyG change patterns over 4 years to observe its long-term effect on the risk of stroke among hypertensive patients. Our baseline results are consistent with previous findings in patients with hypertension [ 31 , 32 ], showing that the highest TyG was in the youngest patients with hypertension. Moreover, our previous work has shown that TG level in the young people is generally higher than in the older, which was also found in the other studies [ 33 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, trajectories were used to present the TyG change patterns over 4 years to observe its long-term effect on the risk of stroke among hypertensive patients. Our baseline results are consistent with previous findings in patients with hypertension [ 31 , 32 ], showing that the highest TyG was in the youngest patients with hypertension. Moreover, our previous work has shown that TG level in the young people is generally higher than in the older, which was also found in the other studies [ 33 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, most of the studies were conducted in relatively healthy population and very few studies have explored the relationship between TyG index and stroke incidence in hypertensive patients at a high risk of stroke. To our knowledge, only in a cohort study among elderly patients with hypertension, Hu et al found a positive association between TyG index and the risk of first stroke [ 31 ]. Furthermore, previous studies in the general population or hypertensive patients only focused on a single TyG measurement without considering the long-term effect of TyG changes over time on stroke.…”
Section: Discussionmentioning
confidence: 99%
“…There were three cross-sectional studies [ 29 , 38 , 40 ] and fifteen cohort studies [ 19 , 21 23 , 31 37 , 39 , 41 43 ], consisting of prospective and retrospective designs, and no randomized controlled trials. The population of the original studies were mainly from China [ 19 , 21 23 , 29 , 31 34 , 36 , 39 , 41 , 43 ], with three from Korea [ 37 , 38 , 40 ], one from Singapore [ 42 ], and one from European [ 35 ]. The primary data sources included the eICU (emergency intensive care unit) Collaborative Research Database [ 36 ], the China National Stroke Registry [ 22 , 39 , 41 ], the UK Biobank cohort [ 35 ], the hospital stroke-related information [ 21 , 23 , 34 , 37 , 38 , 40 , 42 , 43 ], and the community-based or rural population studies [ 19 , 29 , 31 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The population of the original studies were mainly from China [ 19 , 21 23 , 29 , 31 34 , 36 , 39 , 41 , 43 ], with three from Korea [ 37 , 38 , 40 ], one from Singapore [ 42 ], and one from European [ 35 ]. The primary data sources included the eICU (emergency intensive care unit) Collaborative Research Database [ 36 ], the China National Stroke Registry [ 22 , 39 , 41 ], the UK Biobank cohort [ 35 ], the hospital stroke-related information [ 21 , 23 , 34 , 37 , 38 , 40 , 42 , 43 ], and the community-based or rural population studies [ 19 , 29 , 31 33 ]. IS patients included in the analysis had a larger proportion of males, with a mean age greater than 60 years.…”
Section: Resultsmentioning
confidence: 99%
“…In total, our study evaluated 4,405 relevant articles that were initially screened from electronic databases, but only 28 articles met our inclusion criteria, which contained a total of 11,944,688 participants. These 28 studies, involving nineteen cohort studies [10,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and ten case-control/cross-sectional studies [16,18,38,[44][45][46][47][48][49][50] (with one of the articles including both cohort and cross-sectional portions), investigated the risk of cerebrovascular disease in populations with different TyG index. The specific details are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%